Torsional wave dispersion in a finitely pre-strained hollow sandwich circular cylinder - Akbarov, S. D.; Kepceler, T.; Egilmez, M. Mert (ACADEMIC PRESS LTD- ELSEVIER SCIENCE LTD, 2011)
This paper studies torsional wave dispersion in a three-layered (sandwich) hollow cylinder with finite initial strains. The investigations are carried out within the scope of the piecewise homogeneous body model with the use of the three-dimensional linearized theory of elastic waves in initially stressed bodies. The mechanical relations of the materials of the cylinders are described through their harmonic potential. The analytical expression is obtained for the low wavenumber limit values of the torsional wave propagation velocity. The numerical results on the influence of the initial stretching or compression of the cylinders along the torsional wave propagation direction are presented and discussed. (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: MATERIAL COMPOUNDED CYLINDER; NEO-HOOKEAN BODY; INTERFACIAL WAVES; INITIAL STRESSES; HARMONIC-WAVES; ELASTIC MEDIA; PROPAGATION; DEFORMATIONS; STATES; Acoustics; Engineering; Mechanics